The fundamental components of the theory of grace in Kennedy's works - shamsollah seraj; monireh hadadi (حکمت اسرا)
Abstract: The roots and foundations of grace can be recovered and reflected in the works of Kennedy (185-252 AH); Before other Islamic philosophers, he explained the mode of the activity of the God, as the only real agent that gives existence, the agent of the permission of creations, the explanation of the creative verb, the explanation of the formation of the best system in accordance with the previous wisdom of God and the foundation that is suitable for the soul of the exalted of wisdom. Islam has established the theory of grace to explain these issues. Since the prevailing opinion considers Farabi as the first Islamic thinker who discussed the issue of grace, the necessity of the current analytical research is revealed to understand the correct historical development of this issue and to determine the role of Kennedy regarding the issue of grace. So far, no research has been done in this field.